Advances in Graphene-Based Electrode for Triboelectric Nanogenerator - Xie, Bin; Guo, Yuanhui; Chen, Yun; Zhang, Hao; Xiao, Jiawei; Hou, Maoxiang; Liu, Huilong; Ma, Li; Chen, Xin; Wong, Chingping (Nano-Micro Letters, 2024)
With the continuous development of wearable electronics, wireless sensor networks and other micro-electronic devices, there is an increasingly urgent need for miniature, flexible and efficient nanopower generation technology. Triboelectric nanogenerator (TENG) technology can convert small mechanical energy into electricity, which is expected to address this problem. As the core component of TENG, the choice of electrode materials significantly affects its performance. Traditional metal electrode materials often suffer from problems such as durability, which limits the further application of TENG. Graphene, as a novel electrode material, shows excellent prospects for application in TENG owing to its unique structure and excellent electrical properties. This review systematically summarizes the recent research progress and application prospects of TENGs based on graphene electrodes. Various precision processing methods of graphene electrodes are introduced, and the applications of graphene electrode-based TENGs in various scenarios as well as the enhancement of graphene electrodes for TENG performance are discussed. In addition, the future development of graphene electrode-based TENGs is also prospectively discussed, aiming to promote the continuous advancement of graphene electrode-based TENGs. Highlights: 1 Comprehensively reviewed the progress in research on graphene electrode-based triboelectric nanogenerators (TENGs) from two dimensions, including precision processing methods of graphene electrodes and applications of TENGs. 2 Discussed the various applications of graphene electrode-based TENGs in different scenarios, as well as the ways in which graphene electrodes enhance the performance of TENGs. 3 Offered a prospective discussion on the future development of graphene electrode-based TENGs, with the aim of promoting continuous advancements in this field.